2012
DOI: 10.13172/2050-2303-1-1-256
|View full text |Cite
|
Sign up to set email alerts
|

Spinal metastasis subjected to photodynamic therapy: an update.

Abstract: Introduction This is a review of the evidence on the use of photodynamic therapy in the management of bone lesions in spinal metastasis. Materials and methods The literature was searched for relevant articles and the results were examined. The search included ongoing trials that aim to tackle this disease. Results Eight studies were identified in the literature; none were applied on humans. Conclusion Photodynamic therapy is an effective modality in managing osteoblastic and/or osteolytic spinal bone metastasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
(117 reference statements)
0
2
0
Order By: Relevance
“…Preliminary results of an ongoing clinical trial with belomycin/Amphinex have shown good response in different human tumors, including advanced sarcomas [118], supporting further clinical investigation as a possible rescue treatment for relapsed patients. Targeting the insulin-like growth factor system is an attractive treatment option for cancers such as bone sarcomas, in which this pathway plays an important role for tumor development and growth [120].…”
Section: Bleomycin and Amphinexmentioning
confidence: 90%
“…Preliminary results of an ongoing clinical trial with belomycin/Amphinex have shown good response in different human tumors, including advanced sarcomas [118], supporting further clinical investigation as a possible rescue treatment for relapsed patients. Targeting the insulin-like growth factor system is an attractive treatment option for cancers such as bone sarcomas, in which this pathway plays an important role for tumor development and growth [120].…”
Section: Bleomycin and Amphinexmentioning
confidence: 90%
“…To further improve bleomycin efficacy, recently photochemical internalization techniques were used to enhance drug transport into tumor cells and showed promising activity in advanced sarcomas [5,67].…”
Section: Bleomycinmentioning
confidence: 99%